Clinical diagnosis, outcomes and treatment of thiamine deficiency in a tertiary hospital. Issue 1 (January 2022) - Mifsud, François; Messager, Diane; Jannot, Anne-Sophie; Védie, Benoît; Balanant, Nadia Aissaoui; Poghosyan, Tigran; Flamarion, Edouard; Carette, Claire; Lucas-Martini, Léa; Czernichow, Sébastien; Rives-Lange, Claire
Summary: Background: Acute thiamine deficiency can occur in patients with or without history of alcohol abuse and can lead to life-threatening complications. Clinical diagnosis is challenging, often resulting in delayed recognition and treatment. Patients may present with heterogenous symptoms, more diverse than the historical neurological description. Cerebral MRI can contribute to the diagnosis in patients with neurological signs but it is not always feasible in emergency settings. Prompt parenteral supplementation is required to obtain the improvement of symptoms and avoid chronic complications. Aims: To describe the clinical presentation of reported cases of thiamine deficiency, assess prescription and results of cerebral imaging, review treatments that had been prescribed in accordance or not with available guidelines, and study the short-term outcome of these patients. Methods: This is a monocentric retrospective analysis of all reported cases of thiamine deficiency in a French tertiary hospital between January 1st 2008 and December 31st 2018. Results: Fifty-six cases were identified during the study period. Forty-five (80%) patients had a history of alcohol abuse. Most patients were diagnosed based on neurological symptoms but non-specific and digestive symptoms were frequent. Thirty-four percent of patients fulfilled clinical criteria for malnutrition. A brain MRI was performed in 54% of patients and was abnormal in 63% of these cases. Eighty-five percent of patients were treated by parenteral thiamine administration and the supplementation was continued orally in 55% of them. The majority of patients initially received 1000 mg daily of IV thiamine but the dose and duration of thiamine supplementation were variable. At the time of discharge, partial or complete improvement of symptoms was noted in 59% of patients. Conclusion: This study highlights the clinical and radiological heterogeneity of thiamine deficiency. These observations should encourage starting thiamine supplementation early in patients with risk factors or suggestive symptoms even in non-alcoholic patients, and underline the importance of early nutritional support.